Pengantar Media Dakwah Kontemporer - Fauzan Delasta Bramantyo; Andi Abdul Hamzah; Firdaus Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the development process of da'wah media in contemporary times. This research uses a qualitative approach, with the type of literature review research collecting data from books, articles, and credible sources from the internet. The use of media in da'wah is not only limited to traditional methods such as lectures or sermons, but has developed into a more modern and innovative form with the existence of various digital platforms, the potential for disseminating information to the public is getting wider. However, this also brings its own challenges, especially related to ethics in preaching. Therefore, it is important to understand the concept of da'wah media and the history of its development and second, the relevance of the media in the contemporary context, and the ethics that should be upheld in its use. This study discusses the definition of da'wah media as well as the history of its development and the relevance of da'wah media ethics in contemporary times. The results of the study show that the development of da'wah media shows that da'wah media is a means used to convey religious messages to the wider community and transforms from traditional forms such as live lectures and magazines, to digital platforms such as social media, podcasts, and online videos and the ethical relevance of da'wah media covers various aspects, ranging from honesty in conveying information, maintaining harmony between religious communities, to respecting differences of opinion through an inclusive and dialogical approach.